Integration, Game, and Sustainable Development of Shenzhen Port Based on Governmental Regulations - Xuanfei Wang; Shan Liang; Zhenjie Liao (Journal of Mathematics)
The internal integration, game, and sustainable development of Shenzhen Port play key roles in developing a synergy mechanism among Guangdong-Hong Kong-Macau Greater Bay Area (GBA) ports. Using a logistics model, a parameter estimation and evolutionary analysis of Shenzhen Port were performed, revealing that it requires a new impetus to promote growth in its container throughput. Based on the population ecology theory, a two-population Lotka-Volterra model was used to discuss the activity and mutual effect between the western and eastern port areas of Shenzhen Port, quantitatively measuring the varying degrees of the hindering effects between them. To reduce competition and strengthen cooperation, a port game matrix with a punishment mechanism of governmental regulations was created to discuss the internal integration of Shenzhen Port. The results show that, along with the promoting effect of port cooperation on the increase in container throughput, there is a gradual increase in the punishment of speculative behaviours. Government-dominated port cooperation prevents the prisoner’s dilemma in the port activity process. The findings of this study provide quantitative data support and decision-making references for achieving resource complementarity, developing synergy mechanisms, and attaining sustainable development in Shenzhen Port.